Planning Approaches To Preservation And Renovation In Nanluogu Xiang Area - Chuan, Zuo (Journal of Regional and City Planning, 1996)
On the basis of a thorough and detailed investigation into the present condition and communal problems in Nanluogu Xiang area, the City Research Group of the Institute from Architecture and Urban Studies, Tsinghua University, has accomplish some tentative studies and produced some planning policies. This paper attempts to tackle the problems in preservation and renovation of the overall physical environment, in this area. In addition, a further discussion is made on a few common problems, such as the scale and effect of Old City preservation and renovation, redistribution of land value, public participation and support, and protection of interest of residents and the district.Situated in the southeast of Gulou (Drum Tower) of the Old City of Beijing, Nanluogu Xiang neighborhood is surrounded by Di’anmenwai Street, Jiaodaokou South Street, Gulou East Street and Kuanjie Street, covering about 84 hectares’ of land. At present, Hutong are well laid out and courtyard houses nicely preserved in the center of this neighborhood, and the entire neighborhood is one of the most important single—story courtyard house preservation areas in Beijing. .Ju‘er Hutong, which had been partly rehabilitated, lies in the northeastern comer of the neighborhood and takes up 8.2 hectares of land. With the view of working out a preservation and renovation plan of Nanluogu Xiang are, the Inner city research Group from the Institute of Architectural and Urban Studies, Tsinghua University, has conducted a thorough and detailed investigation into the physical condition and communal issues s itch as the present state of land occupation, property ownership and quality of houses, transportation, afforestation, composition and financial situation of residents, and put forward some tentative planning policies regarding the preservation and renovation of this area. This paper attempts to approach several aspects of the issue.